Micro-loans and their impact on the income, housing and unemployment of the beneficiaries - بلدية علاء; يمن منصور (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research deals with the impact that micro-loans can play in improving the income, level of unemployment and housing of the beneficiaries, by studying this type of lending and showing its characteristics, types and difficulties facing this type. This was done by using the statistical analysis of a questionnaire distributed to the beneficiaries of micro-loans in Lattakia Governorate, in addition to applying some simple statistical methods such as one sample test and independent Samples Test. And we found through this study that these loans did not have the expected impact on the level of unemployment of the target groups and on the level of their housing, although there is a clear and statistically significant effect of micro-loans on the income level of the beneficiaries, and perhaps this is the most important goal of the objectives of micro-loans, which is the goal Through which the other goals are met, but insufficient amounts and weak financing lead to a lack of real benefit from loans at the level of unemployment and housing.